Sustainable integrated pest management of vegetable crops - Kumar, Arvind; Pal, Rishi (Indian Horticulture, 2020)
Vegetables crops like brinjal, okra, cabbage, cauliflower, tomato, beans and cucurbit are important vegetables cultivated in India. Several biotic and abiotic factors limit the productivity of vegetables, mainly disease and insect pests. Because of high susceptibility of vegetables to insects, farmers tend to apply chemicals for protective purposes. Also their high profitability combined with a lack of knowledge among the farmers has often led to improper use and hand of synthetic insecticides. This has resulted in great hazards to the environment and ecological consequences like destruction of natural enemy fauna, ill-effect on non-target organisms, residues in consumable product and the health of uses and imbalance between the insect pests and their natural enemies.